Risk factors for syphilis infection among people attending designated STI/RTI clinics in Meghalaya - Verma, Shikha; Pala, Star; Goswami, Aniket; Kharmujai, Ophelia Mary; Nadon, Herman; Warjri, Safeeda G.; Myrthong, Laura Wanda K.; Decruse, Bethabara (International Journal Of Community Medicine And Public Health, 2025)
Background: Syphilis remains a major public health concern in Meghalaya despite the availability of effective diagnostics and treatment. This study aimed to identify behavioral and sociodemographic risk factors associated with syphilis infection among attendees of designated STI/RTI clinics (DSRCs). Methods: A matched case-control study was conducted across six DSRCs between May and June 2023, including 66 confirmed syphilis cases and 263 age-, sex-, and marital status-matched controls. Data on demographics, substance use, sexual behaviour and treatment-seeking were collected using structured interviews. Secondary record-based data (2017-2022) from all DSRCs were analysed to assess district-wise and temporal trends. Results: Most participants were aged 26-35 years (cases: 48.5%; controls: 49.4%) and male (56.1% versus 57.8%). Alcohol use was reported by 56.1% (n=37) of cases and 41.8% (n=110) of controls. Extramarital sexual partnerships were common (72.1% versus 67.9%) and independently associated with syphilis (adjusted OR=2.86; p=0.026). Awareness of STI clinics was low (31.8% versus 35.7%). District-level analysis revealed the highest RPR positivity in East Jaintia Hills (up to 24%), followed by East Khasi Hills (20%) and West Jaintia Hills (9.6%). Conclusions: Extramarital partnerships independently predicted syphilis infection. Strengthening behavioural interventions, partner notification, and district-focused screening is critical to curb transmission.